2018
DOI: 10.5194/gi-7-235-2018
|View full text |Cite
|
Sign up to set email alerts
|

Backpropagation neural network as earthquake early warning tool using a new modified elementary Levenberg–Marquardt Algorithm to minimise backpropagation errors

Abstract: Abstract.A new modified elementary LevenbergMarquardt Algorithm (M-LMA) was used to minimise backpropagation errors in training a backpropagation neural network (BPNN) to predict the records related to the ChiChi earthquake from four seismic stations: Station-TAP003, Station-TAP005, Station-TCU084, and Station-TCU078 belonging to the Free Field Strong Earthquake Observation Network, with the learning rates of 0.3, 0.05, 0.2, and 0.28, respectively. For these four recording stations, the M-LMA has been shown to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Referring to the captions of Figures 7, 8, and 9, the threshold of the predicted error is 11.91 TECu in Figure 8, which is the maximum value of the predicted errors (Note: predicted errors for September 17, 18, and20, 1999, andMay 13, 2003, were not evaluated). In this study, under the condition that the predicted error is greater than 11.91 TECu, the predicted error was identified as a TEC precursor (Lin et al, 2018). The predicted results of the two BPNN models were compared with the results of past related studies in Section 2 to verify the reasonability of the selected threshold, that is, 11.91 TECu.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Referring to the captions of Figures 7, 8, and 9, the threshold of the predicted error is 11.91 TECu in Figure 8, which is the maximum value of the predicted errors (Note: predicted errors for September 17, 18, and20, 1999, andMay 13, 2003, were not evaluated). In this study, under the condition that the predicted error is greater than 11.91 TECu, the predicted error was identified as a TEC precursor (Lin et al, 2018). The predicted results of the two BPNN models were compared with the results of past related studies in Section 2 to verify the reasonability of the selected threshold, that is, 11.91 TECu.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, for the first objective, it is expected that the TEC precursors of these two earthquakes can be detected by predicting the TEC situation using the two BPNN models. A large predicted error can be an indicator for the TEC precursors, according to the results of the study of Lin et al (2018). For the second objective, any TEC precursor is expected to be detected relating to the earthquakes with an ML ≥ 5.0.…”
Section: Objectives Of This Studymentioning
confidence: 97%
See 2 more Smart Citations
“…Numerous studies showed the performance of neural networks in predicting earthquakes. Neural networks have been applied to an early earthquake warning system (EEWS), which is trained using backpropagation with modified Levenberg-Marquardt algorithm to minimize the error rate in the EEWS [3]. The error rate that was tried to be minimized was the error on seismic data amplitude prediction based on the Chi-chi earthquake in Taiwan in 1999.…”
Section: Methodsmentioning
confidence: 99%